Use of in vitro critical inhibitory concentration, a novel approach to predict in vivo synergistic bactericidal effect of combined amikacin and piperacillin against Pseudomonas aeruginosa in a systemic rat infection model - Chan, E. (2014)
10.1007/s11095-006-9783-x